Condicionantes da eficácia do trabalho em equipes de gestão de projetos virtuais - Polete, Ana Carolina Angeli (2012)
There is growing interest from organizations to conduct projects with virtual teams, in order to innovate and seek competitive advantages. Virtual teams are groups of geographically dispersed workers who collaborate on a multitude of tasks. They have common goals and perform interdependent tasks. What distinguishes virtual teams from traditional teams is the fact that its members are not physically close. That is, there are boundaries of space, time and organization. The environment of these project teams is complex, involving often professionals from multiple business functions, from different companies and different expectations. The effectiveness of virtual teams is a subject of growing interest. One factor that may influence the effectiveness of the team is maturity - which can be defined as the state of being fully developed, the proposed understanding or visibility into how success happens, and ways to prevent common problems. Thus, maturity is associated with problems or to avoid confronting them in a positive way (SCHLICHTER, 1999). This study deals with the analysis of the effects of maturity on effectiveness in performing the work of virtual teams in the context of project management. A quantitative study was performed to examine the hypothesis that the higher the maturity level of the virtual team, greater the efficiency in the performance of teamwork. For this, a questionnaire was administered to 100 project managers of virtual teams in a multinational company focused on projects in transport, energy and gas. The results do not support the hypothesis that the high maturity results in greater efficiency. Teams not considered mature in the study were also assessed as effective. This suggests that efficacy is related to other factors that not only maturity. Among these, the study suggests that regular meetings as possible predictors of efficacy should be investigated more intensively in subsequent studies.